2022
DOI: 10.1038/s41592-022-01436-z
|View full text |Cite
|
Sign up to set email alerts
|

Antigen identification and high-throughput interaction mapping by reprogramming viral entry

Abstract: Deciphering immune recognition is critical for understanding a broad range of diseases and for the development of effective vaccines and immunotherapies. Efforts to do so are limited by a lack of technologies capable of simultaneously capturing the complexity of adaptive immunoreceptor repertoires and the landscape of potential antigens. To address this, we present receptor-antigen pairing by targeted retroviruses, which combines viral pseudotyping and molecular engineering approaches to enable one-pot library… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 94 publications
1
29
0
Order By: Relevance
“…Although bulk and single-cell methods are limited to a modest number of antigen–MHC complexes per run, the advent of technologies such as lentiviral transfection assays 28 , 29 provides scalability to up to 96 antigen–MHC complexes through library-on-library screens . However, previous knowledge of the antigen–MHC complexes of interest is still required.…”
Section: State Of the Artmentioning
confidence: 99%
“…Although bulk and single-cell methods are limited to a modest number of antigen–MHC complexes per run, the advent of technologies such as lentiviral transfection assays 28 , 29 provides scalability to up to 96 antigen–MHC complexes through library-on-library screens . However, previous knowledge of the antigen–MHC complexes of interest is still required.…”
Section: State Of the Artmentioning
confidence: 99%
“…There is no need for special organisms or genetic modifications, and the technique can easily be expanded to new antigens and T cell-APC pairs from both mice and humans. This strategy can, for instance, be integrated into validation efforts for antigen discovery and utilized in the investigation of the synapses of newly deorphanized human T cells, a largely unexplored area where tools are scarce [29][30][31][32]. Given that is a two-part system (tag and FlAsH), it also carries the added capability of being inducible at different time points to allow for increased flexibility in interrogating pMHCII-TCR interactions over time.…”
Section: Discussionmentioning
confidence: 99%
“…Birnbaum's team showed that yeast-display-trained models improve the prediction of peptide-binding affinity for pathogen-and tumor-associated peptides. To enable high-throughput screening of antigen-specific TCRs, they developed 'receptor-antigen pairing by targeted retroviruses' (RAPTR), which match TCRs with their cognate antigens based on specific infection of TCR-expressing cells by antigen-displaying viruses 7 . This technology enables the screening of single or polyclonal TCRs and further identification by bulk or single-cell sequencing.…”
Section: Meeting Reportmentioning
confidence: 99%